Whiteness interrupted : white teachers and racial identity in predominantly Black schools - Bell, Marcus, 1983- (Duke University Press, 2021)
"Marcus Bell presents a revealing portrait of white teachers in a majority Black schools to outline how white racial identity is constructed based on localized interactions and the ways whiteness takes a different form in predominantly Black spaces."--